Annual effective dose and excess life time cancer risk assessment from tobacco plants - Boumala, D.; Belafrites, A.; Tedjani, A.; Mavon, Ch; Groetz, J.-E. (Perspectives in science, 2019)
Cigarette smoking is one of the pathways that might cause radiation exposure due to the presence of radioactive elements in tobacco leaves used in the manufacture of cigarettes. From the health point of view, the knowledge of radioactivity content of the various radionuclides in tobacco leaves and their derivative products is important to assess the radiological effects associated with tobacco smoking for smokers. In this work, naturally occurring radionuclides 226Ra, 232Th and 40K and man-made 137Cs were measured in tobacco using gamma-ray spectrometry. Results show that the average concentrations of 226Ra, 232Th and 40K vary from 4.30±0.2 to 11.85±0.7 (average 8.17), 1.35±0.1 to 16.12±0.9 (average 6.08), and 565.6±15.5 to 1235.81±35 (average 908.09)Bqkg−1, respectively. 137Cs activity concentrations were ranged from 0.15±0.01 to 0.67±0.9 (average 0.44)Bqkg−1. The most important radiological parameters, including radium equivalent (Raeq), total annual effective dose (AED) and excess lifetime cancer risk (ELCR) were calculated. For smokers, the total AED resulting from activity concentrations of 226Ra, 232Th and 40K in tobacco samples ranged from 0.44 to 2.29 (average 1.39)mSvy−1, while of 137Cs varied from 0.01 to 0.04 (average 0.025)μSvy−1 and so very little is contributing to the total dose due to inhalation to smokers. ELCR was higher than the world's average of 1.45×10−3 for tobacco and coal samples. The excess lifetime cancer risk ranged from 1.55×10−3 to 8.01×10−3 with an average value of 4.88×10−3 for all tobacco samples under investigation.